Design and Analysis of Integrated Electronic Ballast for HID Lamps Featuring HPF (International Journal of Engineering and Computer Science, 2017)
This paper proposes high-power-factor electronic ballast for metal-halide (MH) lamps. In the proposed circuit, two buck–boost converters and a buck converter are integrated with a full-bridge inverter by sharing the four active switches of the full-bridge inverter. Two active switches are switched at high frequencies, while the other two are switched at lower frequencies. The buck converter is used to step down the DC-link voltage of the full-bridge inverter and filter out the high-frequency components to drive lamps with a low-frequency square-wave (LFSW) current. The buck–boost converters are operated at discontinuous-conduction mode to perform the function of power-factor correction (PFC) to ensure almost unity power factor at the input line. By tactful arrangement of diodes, the DC-link capacitors are discharged in parallel; this helps to operate the high-frequency active switches at a high duty ratio, achieving a small peak value of the PFC-converter current and correspondingly smaller conduction losses. Detailed operation modes and the design equations are provided. Prototype electronic ballast for a 70 W MH lamp is built and tested. Experimental measurements have proven that the proposed electronic ballast has the advantages of high-power factor and being free of acoustic resonance. By integrating the active switches of the converters and the inverter, the proposed electronic ballast is advantageous in terms of cost-effectiveness and high energy-conversion efficiency